Pendidikan Kasih sayang (Rahmah) Dalam Perspektif Al-Qur’an dan Hadis Tarbawi - Lestari, Yanti; Mirza, Iskandar (Jurnal Penelitian Tarbawi: Pendidikan Islam dan Isu-Isu Sosial, 2026)
This study discusses the concept of compassion-based education (rahmah) in the perspective of the Qur’an and Hadith as a response to the tendency of contemporary education that prioritizes cognitive achievement while neglecting moral and humanistic values. The main problem addressed in this study is the gap between Islamic normative teachings that emphasize compassion and the educational practices that are often authoritarian and lacking empathy. This study aims to analyze the concept of rahmah in education based on the Qur’an and Hadith, identify its educational values, and examine its relevance and implications for contemporary Islamic education. This research employs a qualitative approach using library research methods, with primary sources consisting of Qur’anic verses and Hadiths, and secondary sources in the form of classical and contemporary Islamic education literature. The findings show that compassion (rahmah) is a fundamental principle in Islamic education, reflected in the Prophet Muhammad’s educational methods characterized by gentleness, empathy, patience, and moral exemplarity. Compassion-based education contributes to the creation of a humanistic learning environment, strengthens character formation, and supports holistic student development. In conclusion, integrating the values of rahmah into educational practices is essential to realizing the true objectives of Islamic education, namely the development of knowledgeable, ethical, and compassionate individuals. Keywords: compassion-based education; rahmah; qur’an and hadith; islamic education; character education